STYLE IN TRANSLATION AS A PARAMETER IN TQA: A PRAGMATIC PERSPECTIVE - Rahmat Wisudawanto (Universitas Wiralodra, 2024)
Style in translation can be a parameter in translation quality assessment (TQA). The style in translation refers to the translation having the same perspective as the source text. In assessing style in translation, translation does not only focus on the meaning but also the relevance of utterance. The article discusses the translation style based on pragmatic studies. The study used the utterances in the tourism text Solo Calendar of Event 2018 as data since the text has a communication function. The function of the text should be represented in the translation to achieve the same perspective of translation. The style in translation also considers the translator's effort to achieve the equivalence in meaning and relevance of utterance. The style in translation of a pragmatic perspective requires a relevance of communication. The study indicates that the there are two relevance degree, namely translation with strong and weak relevance. Translation with strong relevance indicates that translation can preserve the style of source text. The maintaining of style of source text contribute to the high quality of translation.